2017
DOI: 10.21472/bjbs.040706
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of bitter leaf Vernonia amygdalina Delile (Asterales: Asteraceae) ameliorates testosterone-induced benign prostatic hyperplasia (BPH) in Wistar rats

Abstract: Abstract. Benign prostatic hyperplasia (BPH) is an age-dependent condition involving prostate enlargement which may lead to lower urinary tract symptoms (LUTS). This study was designed to study the ameliorative effect of the aqueous extract of bitter leaf Vernonia amygdalina Delile (Asterales: Asteraceae) on testosterone-induced BPH in a rat model. Thirty adult male Wister rats were randomly divided into six groups (A to F), with BPH induced through a single subcutaneous injection of 5 mg/kg of testosterone pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Vernonia amygdalina Delile (VAD) is an edible vegetable and a valuable medicinal plant that is widespread in Cameroon, Central West Africa. A recent study indicated that an aqueous extract of VAD ameliorated testosterone-induced benign prostatic hyperplasia in Wistar rats [ 18 ]. Previously, Izevbigie (2003) reported that some peptides (edotides) from the aqueous extract of V. amygdalina showed cell growth-inhibitory effects in the prostate cancer cell line, but no effect on normal human peripheral blood mononuclear cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vernonia amygdalina Delile (VAD) is an edible vegetable and a valuable medicinal plant that is widespread in Cameroon, Central West Africa. A recent study indicated that an aqueous extract of VAD ameliorated testosterone-induced benign prostatic hyperplasia in Wistar rats [ 18 ]. Previously, Izevbigie (2003) reported that some peptides (edotides) from the aqueous extract of V. amygdalina showed cell growth-inhibitory effects in the prostate cancer cell line, but no effect on normal human peripheral blood mononuclear cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%